Evaluation of P53 and Some Blood Parameters In Women Diagnosed With Breast Cancer - Kamel, Ghazwan Sabah; Salman, Salih Mahdi; Abood , Walaa Najim (Diyala Journal of Medicine, 2019)
Background:Tumor suppressor genes (including P53) are cancer suppressor genes. Mutations in these genes contribute to the development of cancer ( including breast cancer) since its role in controlling cell growth. Objective: To Evaluate the status of P53 and determination some blood parameters. Patients and Methods: Fifty female patients having primary breast carcinoma or breast mass and their age range from (17- 78 years), were included in this case control study. Other 50 relative to the patient women non breast carcinoma as controls, their age range from (21- 65 years). ELISA test was used to evaluate the status of P53 in serum of breast cancer women and relative control non breast cancer women . Blood samples are collected from both patients women and relative female, 5ml syringe used to collect blood. 3ml of collected venous blood placed in blood tubes with specific gel to facilitate separation of serum and centrifuged at 1400 r.p.m for 10 minutes then serum is collected in collecting tube and store at -20 until use. 2ml of collecting blood placed in EDTA tube for CBC (complete blood account) by Medonic M32 3. Diff Hematology Analyzer, in which WBCs and platelet count included. Results: The titer (Mean ± SD) of p53 in breast cancer women was (140.7 pg/mL ± 60.9 pg/mL) which is less than those of control non breast cancer women which their titer was (192.6 pg/mL ± 285.5 pg/mL) with non-significant difference (P< 0.05) between two groups. The level (Mean ± SD) of total WBC number in breast cancer group was (8.5 pg/mL ± 2.5 pg/mL) x103cells/mm3 which was higher significant (P<0.05) than those of control non breast cancer women (7.5 pg/mL ± 1.4 pg/mL) x103cells/mm3. The level of (Mean ± SD) platelet number of breast cancer women was (344.8 pg/mL ± 116.8 pg/mL) x103cells/mm3 which was higher non-significant(P<0.05) than those of control non breast cancer women (316.7 pg/mL ± 95.8 pg/mL) x103cells/mm3 . There is no correlation between total WBC and platelet number in non breast cancer women but there is non significant correlation in breast cancer women . Lymphocyte and neutrophile number and percentage was significantly higher in breast cancer women than control non breast cancer women. Conclusion: The activity of P53 is decreased which may contributed to cancer while blood parameter were elevated in the serum of breast cancer women.